So many filters, so little time: the development of a search filter appraisal checklist - Glanville, Julie; Bayliss, Sue; Booth, Andrew; Dundar, Yenal; Fernandes, Hasina; Fleeman, Nigel David; Foster, Louise; Fraser, Cynthia; Fry-Smith, Anne; Golder, Su; Lefebvre, Carol; Miller, Caroline; et al. (Journal of the Medical Library Association, 2008)
The authors developed a tool to assess the quality of search filters designed to retrieve records for studies with specific research designs (e.g., diagnostic studies). The UK InterTASC Information Specialists' Sub-Group (ISSG), a group of experienced health care information specialists, reviewed the literature to evaluate existing search filter appraisal tools and determined that existing tools were inadequate for their needs. The group held consensus meetings to develop a new filter appraisal tool consisting of a search filter appraisal checklist and a structured abstract. ISSG members tested the final checklist using three published search filters. The detailed ISSG Search Filter Appraisal Checklist captures relevance criteria and methods used to develop and test search filters. The checklist includes categorical and descriptive responses and is accompanied by a structured abstract that provides a summary of key quality features of a filter. The checklist is a comprehensive appraisal tool that can assist health sciences librarians and others in choosing search filters. The checklist reports filter design methods and search performance measures, such as sensitivity and precision. The checklist can also aid filter developers by indicating information on core methods that should be reported to help assess filter suitability. The generalizability of the checklist for non-methods filters remains to be explored.